Do Mathematics Anxiety and Metacognitive Insight Impact Decision Making in Problem Solving? Systematical Literature Review - Abid Lingga Barensa; Yurizka Melia Sari (Universitas Negeri Surabaya, 2026)
Mathematics anxiety is one of the significant psychological challenges in the process of learning mathematics, especially because of its impact on cognitive abilities and decision-making in problem solving. Previous studies have shown that this anxiety not only decreases academic performance but also affects the efficiency and accuracy of metacognitive monitoring and control. This study aims to examine the relationship between math anxiety, metacognitive insight, and decision-making in solving mathematical problems. The method used is a systematic literature review of 10 scientific articles published in 2021–2025, which includes quantitative, qualitative data, and meta-analysis, focusing on the variables of mathematics anxiety, metacognition, self-efficacy, self-regulation, and problem-solving performance. The results of the review show that math anxiety is negatively related to metacognitive self-confidence and problem-solving performance, but this relationship can be mediated by factors such as self-efficacy, self-regulation, and cognitive activation. The decline in performance is also reinforced by disruption to working memory caused by emotional stress. This study emphasizes the importance of a comprehensive pedagogical approach in building metacognitive abilities while managing emotional factors to improve the effectiveness of mathematics learning.